Role of processing history on the mechanical and electrical behavior of melt-compounded polycarbonate-multiwalled carbon nanotube nanocomposites - Choong, Gabriel Y. H.; Lew, Chun Y.; De Focatiis, Davide S.A. (Wiley, 2015)
This work investigates the effects of primary compounding temperature and secondary melt processes on the mechanical response and electrical resistivity of polycarbonate filled with 3 wt % multiwalled carbon nanotubes (CNT). Nanocomposites were melt compounded in an industrial setting at a range of temperatures, and subsequently either injection molded or compression molded to produce specimens for the measurement of electrical resistivity, surface hardness, and uniaxial tensile properties. Secondary melt processing was found to be the dominant process in determining the final properties. The effects observed have been attributed to structural arrangements of the CNT network as suggested by morphological evidence of optical microscopy and resistivity measurements. Properties were found to be relatively insensitive to compounding temperature. The measured elastic moduli were consistent with existing micromechanical models.